How Does AI Enable Social Engagement for Elderly? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Social isolation is a significant and growing concern among the elderly population, with profound implications for their mental and physical health. As demog...
Keywords: AI in Geriatrics; Enable; Social; Engagement; Artificial Intelligence